Keamanan Manusia dalam Pengaruh Tradisi Dowry di India Terhadap Kekerasan Berbasis Gender di India - Nining Kurnia; Khairur Rizki; Zulkarnain Zulkarnain (Indonesian Journal of Global Discourse, 2023)
Gender-based violence continues to be an issue, especially in India with various causes, one of which is the tradition of giving dowry. The purpose of this study is to analyze how human security is influenced by the dowry tradition that causes acts of gender-based violence in India. This study uses feminism theory and uses the concept of human security to answer the problem formulation because all of them are able to explain the existence of acts of discrimination against women caused by the dowry tradition in India. This study uses a qualitative descriptive approach. The data is taken from secondary sources and analyzed through the interactive model of Miles and Huberman. This study finds the fact that discrimination against women in India as a result of the dowry tradition is difficult to abolish even though the Indian government has made various efforts to overcome it together with international organizations. However, the deep-rooted patriarchal system in Indian society is the main obstacle to tackling acts of discrimination against women to date